A historical climate dataset for southeastern Australia, 1788–1859. (12th September 2014) - Ashcroft, Linden; Gergis, Joëlle; Karoly, David John
<x xml:space="preserve">Abstract</x> There is a significant lack of historical climate data in the Southern Hemisphere compared to the northern latitudes. To address this data scarcity and to improve understanding of regional climate variability, historical instrumental observations were recovered for southeastern Australian (SEA) for the 1788–1859 period. Instrumental observations of temperature, atmospheric pressure, rainfall and raindays were rescued from 39 archival sources, and examined to identify observer biases and inhomogeneities. The rescued data provide continuous information on SEA climate variability from 1826 to 1859, with short periods of observations identified between 1788–1791, 1803–1805 and 1821–1824. Quality control and homogenization of each data source indicates that the historical observations successfully capture regional interannual climate variability. The historical records exhibit high correlations between neighbouring observations and related climate variables. The instrumental observations also display very good agreement with documentary climate reconstructions, further verifying their quality. As an example of how this new historical dataset may be used, regional averages of the observations were calculated to estimate interannual climate variability across SEA from 1826 to 1859. Prolonged dry conditions were identified in various parts of the region during 1837–1843 and 1845–1852, while wet conditions were noted from 1836 to 1838, primarily in southern SEA. Anomalously cold periods were also identified in 1835–1836 and 1848–1849, in general agreement with temperature reconstructions from other regions of the Southern Hemisphere. This new dataset provides a valuable source of subdaily to monthly information on SEA climate variability for future climate analysis, palaeoclimate reconstruction verification and historical studies.